Effects of Discrete Thrust Levels on the Trajectory Design of the BIT-3 RF Ion Thruster-Equipped CubeSat - Alessandro A. Quarta (Applied Sciences)
The use of continuous-thrust propulsion systems allows spacecraft to cover complex space trajectories and to complete missions that would be difficult using chemical thrusters. Among the continuous-thrust propulsion systems proposed in recent decades, solar electric thrusters occupy an important position thanks to the maturity reached by this technology. Technological advances in the miniaturization of spacecraft components allow an electric thruster to be installed even in a small and standardized vehicle such as a CubeSat. In this context, the BIT-3 RF ion thruster is an interesting option that has been recently employed in some space missions for the study of the lunar surface. In the recent literature, the performance of a CubeSat equipped with a propulsion system based on the BIT-3 has been studied considering a simplified model in which the thrust magnitude has a fixed value or varies continuously within a prescribed range. However, the operating levels of a BIT-3 are finite in number. This paper studies the transfer performance of a BIT-3-propelled CubeSat considering the actual operating levels that can be provided by such a thruster. The work analyzes the optimal transfer towards asteroid 2000 SG344 when the electric power is obtained through solar arrays.